Pelatihan desain busana berbasis Adobe Photoshop - Hamidah Suryani; Irmayanti Irmayanti; Kurniati Kurniati (DEDIKASI, 2019)
The partner of this Community Partnership Stimulus Program (PKMS) was The teachers fashion city of Makassar. The problem is lack of knowledge and skills of the teachers and based in design and adobe photoshop.Methods used is: lectures, demonstration, discussion, demonstration and practices directly.Achieved results is ( 1 ) partners have knowledge with design and use application adobe phtoshop, ( 2 ) participants in the jump join the is characterized by the number of participants accordance with the target planned.